Pemanfaatan Alat Pengukur Tinggi dan Berat Badan Digital dalam Menyukseskan Program Imunisasi di Posyandu Desa Kedunglosari - Muhamad Khoirur Roziqin; Machnunah Ani Zulfah; Alfi Nur Laili; Afif Maulana; Eka Dwi Mayangsari (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2022)
One of the health facilities in Kedunglosari village is Taman Posyandu. Taman Posyandu is the front line that provides direct health services and is closest to the community and reaches remote villages that are far from the center of the health facilities provided by each region. Digital Height and Weight Measuring Tool that is designed and realized is a measuring tool that can also provide information on measuring height and weight. This tool is expected so that users do not need to measure height and weight twice and only calculate the ideal weight manually again. This way of measuring weight, ultrasonic sensor to measure height, and weight sensor module (Load Cell HX711) to measure weight. This study aims to determine the response of the community or posyandu participants about the use of digital height and weight devices. In this study can use the method of observation. Researchers came directly to the research location, namely posyandu and demonstrated the development that would be carried out by socializing to related parties. This activity designs a tool that is intended for posyandu parks. The results obtained from this study are the responses of the Kedunglosari village community are very good and open to the development of the measurement tool, which can be seen from the results of the response questionnaire that they strongly agree with the existence of this tool.